Peran Desain Arsitektur dalam Meningkatkan Kualitas Ruang Literasi yang Adaptif - Ulil Aufa Emka (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Literacy spaces play a crucial role in the development of reading, writing, and information comprehension skills. This study examines the roles of architectural design in enhancing the quality of adaptive literacy spaces, focusing on functionality, social interaction, energy efficiency, and sustainability. The research method used is qualitative descriptive through literature study analysis. The findings suggest that the design of literacy spaces should consider zoning, activities, accessibility, the use of local elements, and sustainability. Literacy spaces should also encourage social interaction through inclusive and flexible spatial arrangements. Furthermore, the application of natural lighting and cross ventilation supports energy efficiency. Adaptive design allows spaces to meet the needs of users of various ages and backgrounds. A well-designed literacy space creates an inclusive, comfortable environment that supports a sustainable literacy culture, and also serves as a center for social interaction and effective education.